ALGORITMA MD5 DAN RC5 UNTUK PENGAMANAN FILE PDF - Manuel Luis Belo; Derwin Rony Sina; Yelly Yosiana Nabuasa (Universitas Nusa Cendana, 2020)
Electronic documents are digital file types used to store the important data or information of a person or an institution. There are some of the most widely used document file formats that are. docx,. xlsx,. pptx, and. pdf. Issues that arise when a company, institution or organization that has confidential documents and important data in the form of document files can be accessed by persons or parties who have no authority. A document security solution can use cryptographic onsep. The document file types that can be encrypted are restricted to the Portable Document Format (. pdf) file. In this research is done lock security user input using the algorithm Message Digest 5 (MD5) and binary value multiplier in PDF files using Rivest Code algorithm (RC5). The test results using (i) the same key on a different PDF file indicate that the resulting binary chiperfile is different from the derived binary Plainfile, (ii) the key length of 1 to 8 characters on the same PDF file indicates that binary The chiperfile generated each key length differs from the binary plainfile taken, (iii) a change of 1 character at the beginning, in the middle, and at the end of the input key indicates that the method used is sensitive to the character changes on the key Input. It is known from the level of similarity of binary chiperfile and small/low binary plainfile based on the value of the collation generated per test is (i) 0.205795252, (ii) 0.24692765, (iii) 0.22421886.